ADCS -- spacecraft attitude determination and control - Paluszek, Michael (Elsevier, 2023)
ADCS - Spacecraft Attitude Determination and Control provides a complete introduction to spacecraft control. The book covers all elements of attitude control system design, including kinematics, dynamics, orbits, disturbances, actuators, sensors, and mission operations. Essential hardware details are provided for star cameras, reaction wheels, sun sensors, and other key components. The book explores how to design a control system for a spacecraft, control theory, and actuator and sensor details. Examples are drawn from the author's 40 years of industrial experience with spacecraft such as GGS, GPS IIR, Mars Observer, and commercial communications satellites, and includes historical background and real-life examples.